Effect of applied cadence in repeated sprint cycling on muscle characteristics - Sebastian Klich; Kamil Michalik; Bogdan Pietraszewski; Ernst A. Hansen; Pascal Madeleine; Adam Kawczyński (European Journal of Applied Physiology, 2024)
Purpose This study aimed to investigate physiological responses, muscle–tendon unit properties of the quadriceps muscle, and mechanical performance after repeated sprint cycling at optimal and 70% of optimal cadence. Methods Twenty recreational cyclists performed as first sprint performance cycling test and during subsequent sessions two repeated sprint cycling protocols at optimal and 70% of optimal cadence, in random order. The muscle–tendon unit outcome measures on the dominant leg included muscle thickness, fascicle length ( L f ), pennation angle ( θ p ), and stiffness for the rectus femoris (RF), vastus lateralis (VL), and vastus medialis muscle (VM) at baseline, immediately after repeated sprint cycling, and 1-h post-exercise. Results The results showed an increase in muscle thickness and θ p in RF, VL, and VM for both cadences from baseline to immediately after exercise. The L f decreased in RF (both cadences), while stiffness decreased in RF, VL, and VM at optimal cadence, and in VL at 70% of optimal cadence from baseline to immediately after exercise. Conclusion The present study revealed that the alterations in muscle characteristics were more marked after repeated sprint cycling at optimal cadence compared with a lower cadence most likely as a result of higher load on the muscle–tendon unit at optimal cadence.

Bioplastic degradation and assimilation processes by a novel bacterium isolated from the marine plastisphere - Valérie Barbe; Justine Jacquin; Madeleine Bouzon; Adèle Wolinski; Gabrielle Derippe; Jingguang Cheng; Corinne Cruaud; David Roche; Stéphanie Fouteau; Jean-Louis Petit; Pascal Conan; Mireille Pujo-Pay; et al. (Journal of Hazardous Materials, 2024)

Knee joint vibroarthrography of asymptomatic subjects during loaded flexion-extension movements - Rasmus Elbæk Andersen; Lars Arendt-Nielsen; Pascal Madeleine (Medical & Biological Engineering & Computing, 2018)

Effects of a Worksite Supervised Adapted Physical Activity Program on Trunk Muscle Endurance, Flexibility, and Pain Sensitivity Among Vineyard Workers - Romain Balaguier; Pascal Madeleine; Kévin Rose-Dulcina; Nicolas Vuillerme (Journal of Agromedicine, 2017)

Variability in spatio-temporal pattern of trapezius activity and coordination of hand-arm muscles during a sustained repetitive dynamic task - Afshin Samani; Divya Srinivasan; Svend Erik Mathiassen; Pascal Madeleine (Experimental Brain Research, 2017)

Influence of PAHs among other coastal environmental variables on total and PAH-degrading bacterial communities - Caroline Sauret; Marc Tedetti; Catherine Guigue; Chloé Dumas; Raphaël Lami; Mireille Pujo-Pay; Pascal Conan; Madeleine Goutx; Jean-François Ghiglione (Environmental Science and Pollution Research, 2016)

Effects of concurrent physical and cognitive demands on muscle activity and heart rate variability in a repetitive upper-extremity precision task - Divya Srinivasan; Svend Erik Mathiassen; David M. Hallman; Afshin Samani; Pascal Madeleine; Eugene Lyskov (European Journal of Applied Physiology, 2016)

Ipsilateral resistance exercise prevents exercise-induced central sensitization in the contralateral limb: a randomized controlled trial - Mahdi Hosseinzadeh; Afshin Samani; Ole K. Andersen; Kazunori Nosaka; Lars Arendt-Nielsen; Pascal Madeleine (European Journal of Applied Physiology, 2015)

Functional connectivity between core and shoulder muscles increases during isometric endurance contractions in judo competitors - Adam Kawczyński; Afshin Samani; Dariusz Mroczek; Paweł Chmura; Wiesław Błach; Juliusz Migasiewicz; Sebastian Klich; Jan Chmura; Pascal Madeleine (European Journal of Applied Physiology, 2015)

Pain sensitivity is normalized after a repeated bout of eccentric exercise - Mahdi Hosseinzadeh; Ole K. Andersen; Lars Arendt-Nielsen; Pascal Madeleine (European Journal of Applied Physiology, 2013)

The association between health and sickness absence among Danish and non-Western immigrant cleaners in Denmark - Isabella G. Carneiro; Charlotte D. N. Rasmussen; Marie B. Jørgensen; Mari-Ann Flyvholm; Kasper Olesen; Pascal Madeleine; Dorte Ekner; Karen Søgaard; Andreas Holtermann (International Archives of Occupational and Environmental Health, 2013)

Gender effects on the coordination of subdivisions of the trapezius muscle during a repetitive box-folding task - Thorbjørn I. Johansen; Afshin Samani; David M. Antle; Julie N. Côté; Pascal Madeleine (European Journal of Applied Physiology, 2013)

Eccentric exercise inhibits the H reflex in the middle part of the trapezius muscle - Steffen Vangsgaard; Lars T. Nørgaard; Brian K. Flaskager; Karen Søgaard; Janet L. Taylor; Pascal Madeleine (European Journal of Applied Physiology, 2013)

Pressure pain sensitivity maps, self-reported musculoskeletal disorders and sickness absence among cleaners - Asbjørn Thalund Binderup; Andreas Holtermann; Karen Søgaard; Pascal Madeleine (International Archives of Occupational and Environmental Health, 2011)

Advanced biofeedback from surface electromyography signals using fuzzy system - Afshin Samani; Andreas Holtermann; Karen Søgaard; Pascal Madeleine (Medical & Biological Engineering & Computing, 2010)

Active biofeedback changes the spatial distribution of upper trapezius muscle activity during computer work - Afshin Samani; Andreas Holtermann; Karen Søgaard; Pascal Madeleine (European Journal of Applied Physiology, 2010)

Experimental pain leads to reorganisation of trapezius electromyography during computer work with active and passive pauses - Afshin Samani; Andreas Holtermann; Karen Søgaard; Pascal Madeleine (European Journal of Applied Physiology, 2009)

Longitudinal and transverse propagation of surface mechanomyographic waves generated by single motor unit activity - Corrado Cescon; Pascal Madeleine; Dario Farina (Medical & Biological Engineering & Computing, 2008)

Changes in the degree of motor variability associated with experimental and chronic neck–shoulder pain during a standardised repetitive arm movement - Pascal Madeleine; Svend Erik Mathiassen; Lars Arendt-Nielsen (Experimental Brain Research, 2008)

Time to task failure in shoulder elevation is associated to increase in amplitude and to spatial heterogeneity of upper trapezius mechanomyographic signals - Pascal Madeleine; Dario Farina (European Journal of Applied Physiology, 2007)

Enhanced temporal summation of pressure pain in the trapezius muscle after delayed onset muscle soreness - Hongling Nie; Lars Arendt-Nielsen; Pascal Madeleine; Thomas Graven-Nielsen (Experimental Brain Research, 2006)

The effects of neck–shoulder pain development on sensory–motor interactions among female workers in the poultry and fish industries. A prospective study - Pascal Madeleine; Birthe Lundager; Michael Voigt; Lars Arendt-Nielsen (International Archives of Occupational and Environmental Health, 2003)

Upper trapezius muscle mechanomyographic and electromyographic activity in humans during low force fatiguing and non-fatiguing contractions - Pascal Madeleine; Dario Farina; Roberto Merletti; Lars Arendt-Nielsen (European Journal of Applied Physiology, 2002)

Shoulder muscle co-ordination during chronic and acute experimental neck-shoulder pain. An occupational pain study - Pascal Madeleine; Birthe Lundager; Michael Voigt; Lars Arendt-Nielsen (European Journal of Applied Physiology, 1999)

Subjective, physiological and biomechanical responses to prolonged manual work performed standing on hard and soft surfaces - Pascal Madeleine; Michael Voigt; Lars Arendt-Nielsen (European Journal of Applied Physiology, 1997)